2002
DOI: 10.2106/00004623-200208000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in the Forefoot of Individuals with Diabetes and a Prior Plantar Ulcer

Abstract: Structural changes in the forefoot of individuals with diabetes and a prior plantar ulcer. Background: Plantar ulcers produced by diabetic foot disease are devastating and costly. Better understanding of the ulcer-producing process is important to improve detection of feet that are at risk and to improve intervention. We identified and quantified soft-tissue and osseous structural changes in the forefoot of diabetic patients with a prior plantar ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(72 citation statements)
references
References 29 publications
2
68
2
Order By: Relevance
“…One group developed measures of foot shape from scans of diabetic feet; they determined which forefoot structural parameters could be used to predict high plantar pressure 26 or explain past ulceration. 25 However, this group used different parameters (e.g., calcaneal inclination and metatarsal inclination) than our study, and their data were non-weightbearing, making comparison to our work difficult. Grasso and Scarfi (1993) employed transverse and coronal CT scans to study plantar arch alterations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…One group developed measures of foot shape from scans of diabetic feet; they determined which forefoot structural parameters could be used to predict high plantar pressure 26 or explain past ulceration. 25 However, this group used different parameters (e.g., calcaneal inclination and metatarsal inclination) than our study, and their data were non-weightbearing, making comparison to our work difficult. Grasso and Scarfi (1993) employed transverse and coronal CT scans to study plantar arch alterations.…”
Section: Discussionmentioning
confidence: 82%
“…Others have examined plantar and coronal CT scans for differences due to foot type, but the scans were non-weightbearing, the measures were subjective, and no statistical analysis was performed. 24 Recently, CT scans have been used to demonstrate that diabetic subjects had increased metatarsophalangeal extension at the first, second, and third rays 25 and that hammertoe deformity was the strongest predictor of increased plantar pressure. 26 However, both studies employed a noload condition, their measures had a subjective component (the placement of the measurement lines), and foot type classification was not the aim.…”
Section: Introductionmentioning
confidence: 99%
“…The ICCs for these variables were high (Ͼ0.98), which demonstrates that these variables can be assessed in a reproducible way. Small limits of agreement are important for regression analyses or correlation coefficients computed between variables of foot structure and/or foot function (3,5,6,15,16) because the outcomes from these analyses are determined by the scatter of individual cases.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of structural changes and deformity in the diabetic foot have been obtained using different in vivo imaging techniques, such as ultrasound (3,17), radiography (18), and computed tomography (CT) (6,16,19,20). Saltzman et al (21) determined the interobserver variability of radiographic foot measurements in nondiabetic subjects and found a 95% limit for the MTP joint angle of 6°, which is higher than the limit in the present study (Ͻ3.0°).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Ulceration over the prominent first metatarsal head is a frequent problem. [11][12][13][14] Increased pressure under the first metatarsal head is thought to result from an imbalance of the three extrinsic muscles to the first ray, extensor hallucis longus (EHL), flexor hallucis longus (FHL) and peroneus longus and intrinsic muscle weakness. 15,16 A cadaver study 16 showed that overaction of the EHL raised the pressure under the first metatarsal head.…”
mentioning
confidence: 99%